Co-designing with a community of older learners for over 10 years by moving user-driven participation from the margin to the centre. Issue 1 (2nd January 2018) - Righi, Valeria; Sayago, Sergio; Rosales, Andrea; Ferreira, Susan M.; Blat, Josep
Abstract: This paper addresses a gap in the Participatory Design (PD) literature, wherein more research on the long-term impact of design projects is warranted. This paper reflects on a 10-year study that intertwined ethnography and 2 PD projects in a community of older learners. Although the goal of our study was to design new digital technologies, the process of designing them presented us with opportunities that gave rise to new non-digital practices, which turned out to be the legacy and most significant outcomes of the PD projects. This result invited us to review the trajectory that led to these outcomes. Our analysis shows that the most important legacy aspect of the projects arose from unexpected forms of user—driven participation that we allowed to co-exist together with those practices more related to the design goals of the PD projects. Drawing upon our results, this paper posits that engagement with PD participants that unfolds over an extended period of time is instrumental in facilitating the development of participation, understanding more deeply long-lasting project outcomes, and legitimising forms of participation that are not directly related to project/design goals.